2023
DOI: 10.1007/s00424-023-02809-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the effects of cigarette smoke versus next-generation tobacco and nicotine product extracts on inflammatory biomarkers of human monocytes

Abstract: Monocytes exhibiting a pro-inflammatory phenotype play a key role in adhesion and development of atherosclerotic plaques. As an alternative to smoking, next-generation tobacco and nicotine products (NGP) are now widely used. However, little is known about their pro-inflammatory effects on monocytes. We investigated cell viability, anti-oxidant and pro-inflammatory gene and protein expression in THP-1 monocytes after exposure to aqueous smoke extracts (AqE) of a heated tobacco product (HTP), an electronic cigar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…This section will discuss those studies that utilized cells derived from the cardiovascular system. Four articles were identified that utilized bubbled liquid extracts to compare the in vitro effects of HTPs with cigarettes in cell lines derived from the cardiovascular system [ 40 , 87 - 90 ]. As mentioned previously, when investigating cardiovascular endpoints, bubbled liquid extract exposure is more reflective of exposure to those constituents that are absorbed into the blood after product use and then maybe transported throughout the cardiovascular system.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This section will discuss those studies that utilized cells derived from the cardiovascular system. Four articles were identified that utilized bubbled liquid extracts to compare the in vitro effects of HTPs with cigarettes in cell lines derived from the cardiovascular system [ 40 , 87 - 90 ]. As mentioned previously, when investigating cardiovascular endpoints, bubbled liquid extract exposure is more reflective of exposure to those constituents that are absorbed into the blood after product use and then maybe transported throughout the cardiovascular system.…”
Section: Reviewmentioning
confidence: 99%
“…In the fourth study, the effects of liquid extracts produced from the IQOS HTP on a human monocytic (THP-1) cell line were investigated [ 90 ]. Whole smoke/aerosol from the 3R4F Kentucky reference cigarette, IQOS HTP, and an EVP (Vype) were bubbled into the cell culture medium.…”
Section: Reviewmentioning
confidence: 99%